PELAKSANAAN PEMBERIAN REMISI TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS I CIPINANG - Idrus, Norman Syahdar; Sukarmini, Wien (Jurnal Yuridis, 2016)
Based on the results of this study concluded that remission is one of the rights of prisoners, which is given by the Government that proposal conducted by the Head of Prison Class I Cipinang. Remission granted to prisoners in prison is a Class I Cipinang common form of Remission and remission particular, there is no additional remission. Remission granted to prisoners at Prison Class I Cipinang not always run on time. Factors constraints found in these remissions due to the unpreparedness of the staff at the Regional Office of the Ministry of Justice and Human Rights DKI Jakarta in processing the data submitted by the Head of the Prison Class I Cipinang, giving rise to the term remissions are not recognized in subsequent legislation, as general remission aftershocks, aftershocks Eid special remission, remission special Christmas aftershocks and subsequent remission special Vesak. Other factors are present in the affected inmates self disciplined.